STRATEGI DALAM MENGURANGI KECEMASAN PESERTA DIDIK PADA KETERAMPILAN BERBICARA BAHASA ARAB - Nurauliya Rohali; Adi Fadli (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The low interest in learning and high psychological resistance of students when instructed to express ideas verbally underlie the writing of this article. These operational issues trigger excessive emotional distress, instructional resistance, and verbal nervousness due to the infrequent use of verbalization of foreign drafts in daily cyber interactions. The main focus of this scientific study is to identify comprehensive factors causing linguistic barriers and dissect draft solution strategies to reduce mental stress in Arabic speaking skills. The steps of this qualitative research, using the literature review type, were carried out through a structured search of draft secondary literature. The data collection procedure collected reputable scientific journal articles published between 2020 and 2025, which were then analyzed using interactive thematic data reduction. Theoretically, the research findings reveal that anxiety is triggered by a combination of internal factors such as low self-esteem and external factors such as the educator's rigid personality and fear of being ridiculed by classmates. The main conclusion confirms that the innovative draft of a supportive teaching method that does not judge pronunciation errors has proven highly reliable in maintaining the stability of students' mental health. Educators are recommended to design a continuous adaptive small group discussion draft program. ABSTRAK Rendahnya minat belajar serta tingginya resistensi psikologis peserta didik sewaktu diinstruksikan mengekspresikan gagasan secara verbal melatarbelakangi penulisan artikel ini. Masalah operasional tersebut memicu timbulnya distres emosional berlebih, penolakan instruksional, serta kegugupan verbal akibat jarangnya verbalisasi draf asing tersebut digunakan dalam interaksi siber harian. Fokus utama kajian ilmiah ini adalah mengidentifikasi faktor komprehensif penyebab hambatan linguistik serta membedah draf strategi solutif dalam mereduksi ketegangan mental pada keterampilan berbicara bahasa Arab. Langkah-langkah penelitian kualitatif dengan jenis studi kepustakaan (literature review) ini dioperasikan melalui penelusuran draf literatur sekunder secara terstruktur. Prosedur pengumpulan data menghimpun artikel jurnal ilmiah bereputasi dalam rentang publikasi tahun 2020 hingga 2025, yang selanjutnya dianalisis menggunakan reduksi data tematik secara interaktif. Temuan penelitian secara teoretis menyingkap bahwa kecemasan dipicu oleh kombinasi faktor internal berupa rendahnya self-esteem serta faktor eksternal seperti kepribadian kaku pendidik dan ketakutan diejek oleh teman sekelas. Simpulan utama menegaskan bahwa draf inovasi metode pengajaran suportif yang tidak menghakimi kesalahan pelafalan terbukti sangat andal dalam memelihara stabilitas kesehatan mental siswa. Pendidik direkomendasikan merancang program draf diskusi kelompok kecil adaptif secara berkelanjutan.